2, 4-D (Ethyl ester) poisoning: experience at a tertiary care centre in Northern India. Issue 1 (21st December 2007) - Bhalla, A; Suri, V; Sharma, N; Mahi, S; Singh, S
Abstract : 2, 4-Dichlorphenoxyacetic acid (2, 4-D) is a selective herbicide widely used to kill broad-leaved plants in wheat cultivation. Only a few cases of documented poisoning cases with this compound have been reported from India. Since the initial manifestations are not very different from anticholinesterase poisoning, the chances of misdiagnosis are high. Anticholinesterase compounds are the most commonly used insecticides and are implicated as the commonest cause of agrochemical poisoning in India. This report aims to make physicians aware that not all cases of agrochemical poisoning are caused by anticholinesterase insecticides. Efforts must be made to correctly identify the offending compound for appropriate management.